2020
DOI: 10.3390/ijms21144864
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Natural Extracellular Matrix: Genipin Cross-Linked Adipose-Derived Stem Cell Extracellular Matrix Gel for Tissue Engineering

Abstract: The cell-derived extracellular matrix (ECM) is associated with a lower risk of pathogen transfer, and it possesses an ideal niche with growth factors and complex fibrillar proteins for cell attachment and growth. However, the cell-derived ECM is found to have poor biomechanical properties, and processing of cell-derived ECM into gels is scarcely studied. The gel provides platforms for three-dimensional cell culture, as well as injectable biomaterials, which could be delivered via a minimally invasive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…Thus, both of them are considered as a viscoelastic solid [ 173 ]. Similar results were obtained in the study of Nyambat et al, where collagen hydrogels crosslinked by genipin showed increased stiffness and complex viscosity, while the cell morphology and viability of incorporated adipose-derived stem cells were not significant [ 183 ].…”
Section: Resultssupporting
confidence: 87%
“…Thus, both of them are considered as a viscoelastic solid [ 173 ]. Similar results were obtained in the study of Nyambat et al, where collagen hydrogels crosslinked by genipin showed increased stiffness and complex viscosity, while the cell morphology and viability of incorporated adipose-derived stem cells were not significant [ 183 ].…”
Section: Resultssupporting
confidence: 87%
“…First, when the hydrogel encounters the wound, it changes from liquid to solid to form a physical barrier to prevent further blood flow. Its potential mechanism may be as described by Nyambat Batzaya [ 51 ]. Both the storage modulus (G′) and the loss modulus (G″) increase with the temperature rise from 10°C to 37°C in hydrogels, promoting the transformation from liquid phase to solid phase.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular matrix (ECM) hydrogel is a promising regenerative material that can effectively promote the repair of tissue defects. As previously reported [ 51 ], the entire ECM contains proteoglycans, growth factors, and matricellular proteins, including collagens, elastin, laminin, fibronectin, hyaluronan, heparan, basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), and thrombospondin. Among them, a major component of ECM is collagen.…”
Section: Introductionmentioning
confidence: 93%
“…Mechano-physical re-engineering could be achieved by culturing ECM-secreting cells in 3D sacrificial hydrogels (Yuan et al, 2018), on micro-molds (Schell et al, 2016), and micro-and nano-grooves (Ozguldez et al, 2018;Almici et al, 2020;Yang et al, 2020), forcing cell reorganization and leading to ECM assemblies with unique architectures (i.e., parallel fiber alignment). ECM postprocessing, such as cross-linking, could further alter ECM stiffness (Subbiah et al, 2016) or the overall presentation of CD-ECM.In particular, cross-linking of pepsin-solubilized CD-ECM with genipin resulted in the formation of hydrogels (Nyambat et al, 2020), Changes in biochemical and mechano-physical properties of the ECM let to changes in gene expression and behavior of reseeded cells (Kim et al, 2015;Ozguldez et al, 2018;Sart et al, 2020).…”
Section: Engineering and Characterization Of Cd-ecm To Study Ecm Physmentioning
confidence: 99%
“…ECM postprocessing, such as cross-linking, could further alter ECM stiffness ( Subbiah et al, 2016 ) or the overall presentation of CD-ECM. In particular, cross-linking of pepsin-solubilized CD-ECM with genipin resulted in the formation of hydrogels ( Nyambat et al, 2020 ), Changes in biochemical and mechano-physical properties of the ECM let to changes in gene expression and behavior of reseeded cells ( Kim et al, 2015 ; Ozguldez et al, 2018 ; Sart et al, 2020 ).…”
Section: Applications Of Cd-ecmmentioning
confidence: 99%